Emergency Medicine Resident Assessment of the Emergency Ultrasound Milestones and Current Training Recommendations. (18th February 2017) - Stolz, Lori A.; Stolz, Uwe; Fields, J. Matthew; Saul, Turandot; Secko, Michael; Flannigan, Matthew J.; Sheele, Johnathan M.; Rifenburg, Robert P.; Weekes, Anthony J.; Josephson, Elaine B.; Bedolla, John; Resop, Dana M.; et al.
Abstract: Objectives: Emergency ultrasound (EUS) has been recognized as integral to the training and practice of emergency medicine (EM). The Council of Emergency Medicine Residency‐Academy of Emergency Ultrasound (CORD‐AEUS) consensus document provides guidelines for resident assessment and progression. The Accredited Council for Graduate Medical Education (ACGME) has adopted the EM Milestones for assessment of residents' progress during their residency training, which includes demonstration of procedural competency in bedside ultrasound. The objective of this study was to assess EM residents' use of ultrasound and perceptions of the proposed ultrasound milestones and guidelines for assessment. Methods: This study is a prospective stratified cluster sample survey of all U.S. EM residency programs. Programs were stratified based on their geographic location (Northeast, South, Midwest, West), presence/absence of ultrasound fellowship program, and size of residency with programs sampled randomly from each stratum. The survey was reviewed by experts in the field and pilot tested on EM residents. Summary statistics and 95% confidence intervals account for the survey design, with sampling weights equal to the inverse of the probability of selection, and represent national estimates of all EM residents. Results: There were 539 participants from 18 residency programs with an overall survey response rate of 85.1%. EM residents considered several applications to be core applications that were not considered core applications by CORD‐AEUS (quantitative bladder volume, diagnosis of joint effusion, interstitial lung fluid, peritonsillar abscess, fetal presentation, and gestational age estimation). Of several core and advanced applications, the Focused Assessment with Sonography in Trauma examination, vascular access, diagnosis of pericardial effusion, and cardiac standstill were considered the most likely to be used in future clinical practice. Residents responded that procedural guidance would be more crucial to their future clinical practice than resuscitative or diagnostic ultrasound. They felt that an average of 325 (301–350) ultrasound examinations would be required to be proficient, but felt that number of examinations poorly represented their competency. They reported high levels of concern about medicolegal liability while using EUS. Eighty‐nine percent of residents agreed that EUS is necessary for the practice of EM. Conclusions: EM resident physicians' opinion of what basic and advanced skills they are likely to utilize in their future clinical practice differs from what has been set forth by various groups of experts. Their opinion of how many ultrasound examinations should be required for competency is higher than what is currently expected during training.